The TikTok Illusion: A Systematic Review Why Short-Form Video Marketing is Overhyped and Unsustainable for Brands - Handayanti, Tri (Samudra Publisher, 2025)
The rapid growth of TikTok and short-form video platforms has transformed the digital marketing landscape, driving brands to invest heavily in content designed for virality and engagement. However, there is growing concern that such strategies, while effective in the short term, may not offer sustainable value for long-term brand development. This study conducted a systematic literature review (SLR) of 20 peer-reviewed articles published between 2020 and 2025 to evaluate three main research questions: (RQ1) whether the current literature addresses the impact of TikTok’s algorithm, (RQ2) to what extent TikTok marketing is measured or analyzed, and (RQ3) how short videos are addressed as a marketing medium. The research findings indicate that while most studies acknowledge the power of TikTok's algorithm in influencing content visibility, there is a lack of depth in measuring marketing outcomes beyond surface metrics such as views and likes. Additionally, short videos are often viewed as a novelty rather than a sustainable branding tool. Content fatigue, low message retention, and algorithm uncertainty all contribute to the limitations of short-form video marketing. This article argues that the current enthusiasm for TikTok may be overblown and encourages brands to adopt more diverse and resilient digital strategies to ensure long-term effectiveness.